Pendampingan Manajemen Keuangan Keluarga pada Era New Normal - Putria, Uus (Sivitas : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2023)
The low ability to manage people’s finances can be seen from the low level of saving, investment and high levels of public consumption. Consumptive behavior. Family financial management is very important for the welfare of society and the economic progress of a country, especially in this new normal era. A high understanding of family financial management means that Indonesians can be wiser to use money, not trapped by consumerism traps, debt, bankruptcy and even poverty. Related to this, universities must respond by starting to literate family financial management in the new normal era. To respond to family financial management in the new normal era, universities must provide family financial management assistance in the new normal era to each family. In this service using the Participation Action Research (PAR) method, by approaching the community. By means of observation, interaction, interviews and documentation descriptively on family financial problems. This assistance has resulted in the fact that people still do not know much about family financial management in the new normal era, so there are negative impacts experienced by them. Assistance on family financial management must continue to be carried out by universities as a forum for community service.